A GRAFIA DAS VOGAIS TÔNICAS ANTERIORES E POSTERIORES NÃO-ALTAS NUMA CLASSE DE ALFABETIZAÇÃO (Polifonia, 1995)
ABSTRACT: Through participant observation, fieldnotes and audio-taped data, the author describes the interaction between children and tehir teacher in a literacy classroom of a public school in Cuiabá (Brazil). She attempts to understand how the actors interact in the process of teaching and learning to write the front vowels [E e] and the back vowels [O o] in stressed syllables. In the first part, she reminds us of the grammarians' dilema to represent these sounds in grammar books. In the second part, she follows the teacher's dilemma in teaching her children to write them.